Polymerase chain reaction using 16S rRNA gene sequences distinguishes the two biovars of Ureaplasma urealyticum. - Robertson, J A (1993)
Several fundamental phenotypic and genotypic differences have separated strains of the genital mycoplasma Ureaplasma urealyticum into two clusters or biovars. However, the lack of an easily performed and unambiguous test to discriminate between them has hampered investigation of the relationship between these biovars and disease. We determined the 16S rRNA nucleotide sequence of U. urealyticum 27, the serovar 3 standard and representative of the parvo biovar (serovars 1, 3, 6, and 14). This sequence was compared with the published sequence of U. urealyticum T960, which is the type strain and the serovar 8 standard and is representative of the T960 biovar which is composed of the 10 intervening serovars. Homology between the two sequences was 98.8%; differences were exploited to provide primers for biovar-specific polymerase chain reactions (PCRs). The results of these reactions placed all 14 serovar standard strains into the correct biovar. The PCRs were also applied to 10 cloned and 8 noncloned isolates that had been serotyped earlier. For 16 of them, we deduced their biovars from the serotyping data and then confirmed them by PCR. One unpredictable isolate and one nonserotypeable isolate were also classified as to biovar. Thus, we have developed a method for biotyping U. urealyticum that is applicable to both laboratory-adapted strains and wild-type isolates and that is appropriate for testing large numbers of clinical isolates. The amplification by the T960 biovar PCR protocol of DNAs from ureaplasmas of animals and certain Mycoplasma species suggested that the parvo biovar has diverged from the mainstream of the evolution of this clade.